DINASTI SELJUK DALAM SEJARAH PERADABAN ISLAM - Alawiah, Tuti; Sofiatunnaziah, Sofiatunnaziah; Burhanudin, Burhanudin; Sujana, Ahmad Maftuh (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2025)
In the 11th century CE, the Islamic world faced a critical period marked by the decline of the Abbasid Caliphate, political fragmentation, and external pressures from non-Muslim powers. The Seljuk Dynasty, originating from the Oghuz Turks, emerged as a transformative force that reshaped the political and social landscape of the Islamic world. Under leaders such as Tughril Beg and Alp Arslan, the Seljuks consolidated power in Persia and Iraq, reinforced the authority of the Abbasid Caliphate, and expanded Islamic influence into Anatolia. The dynasty not only acted as a savior against external threats but also served as an internal unifier through administrative reforms, the establishment of educational institutions (such as the Nizamiyah Madrasahs), and the promotion of scientific development. This article aims to analyze the Seljuk Dynasty’s contributions to the medieval Islamic world, the factors behind their rise, and the dynamics of their eventual decline leading to political fragmentation. Utilizing historical approaches and analysis of primary and secondary sources, this study highlights the crucial role of the Seljuks in shaping classical Islamic civilization.